Integration of pastoral fencing areas in sheep breeding systems in the Algerian steppe. - Hadbaoui, Ilyes; Khaouani, Boumedienne; Berrabah, Djamel Edine; Safi, Rekia; Zemour, Hafidh (Annals of Arid Zone, 2023)
The aim of this novel study is to examine theincorporation of pastoral fencing areas as a forage resource inthe management of sheep herds in the Algerian steppe areas.In the quest to reduce feed costs during specific periods,several sheep breeders in the Algerian steppe have resortedto rent pastoral fencing lands. The research methodologyemployed consists of interviews with fencing area rentersand floristic surveys conducted prior to the opening periodof the pastoral fencing. Fencing areas of M’Kimen and Saouasin Tiaret region were selected for this study due to its agropastoral potential. The findings of the study reveal that theproblem of animal overstocking on rangelands is present evenin rangelands controlled by fencing. In spite of the measurestaken to control the fenced areas, the rangelands meet only afraction of the feed requirements for the flocks, specifically25% for M’Kimen and 38.4% for Saouas. The results of thisinvestigation contribute to the scientific understanding ofenhancing the management mechanisms of pastoral fencinglands and the overall development of sheep breedingprograms in the steppe.